Chronic mania associated with left hippocampal atrophy. Issue 5 (8th October 2013) - Chakraborty, Nandini; Miramontes, Carmen
Abstract Abnormalities in the hippocampus have been implicated in the pathophysiology of bipolar disorder. Dr Chakraborty and Carmen Miramontes report an atypical presentation of bipolar disorder with chronic mania (lasting more than two years) in a patient with a history of head injury and evidence of left hippocampal atrophy on neuroimaging.